Case study on seismic tunnel response - Kontoe,S; Zdravkovic,L; Potts,DM; Menkiti,CO (Canadian Geotechnical Journal, 2008)
This paper presents a case study of the Bolu highway twin tunnels that experienced a wide range of damage during the 1999 Duzce earthquake in Turkey. Attention is focused on a particular section of the left tunnel that was still under construction when the earthquake struck and that experienced extensive damage during the seismic event. Static and dynamic plane strain finite element (FE) analyses were undertaken to investigate the seismic tunnel response at two sections and to compare the results with the post-earthquake field observations. The predicted maximum total hoop stress during the earthquake exceeds the strength of shotcrete in the examined section. The occurrence of lining failure and the predicted failure mechanism compare very favourably with field observations. The results of the dynamic FE analyses are also compared with those obtain by simplified methodologies (i.e. two analytical elastic solutions and quasi-static elasto-plastic FE analyses). For this example, the quasi-static racking analysis gave thrust and bending moment distributions around the lining that differed significantly from those obtained from full dynamic analyses. However, the resulting hoop stress distributions were in reasonable agreement.